2022
DOI: 10.1029/2021ef002642
|View full text |Cite
|
Sign up to set email alerts
|

Improved Water Savings and Reduction in Moist Heat Stress Caused by Efficient Irrigation

Abstract: Intensive agriculture and irrigation play a crucial role in the food security of India. However, irrigation has considerably impacted regional climate and groundwater sustainability. Notwithstanding the profound implications of irrigation on dry and moist heat and groundwater depletion, the role of efficient irrigation on moist heat stress reduction and water savings remains unexplored. Here, we use observations and simulations from the Weather Research Forecasting (WRF) model to examine the impact of efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…These relationships point to the conclusion that a drier land surface leads to worsened heat stress. Conversely, some recent studies have argued that droughts generally decrease heat stress because of the effect of reduced humidity 11 , while irrigation increases heat stress because of the effect of increased humidity [12][13][14][15] . This discrepancy has potentially major implications, as some climate adaptation actions intended to reduce heat stress, such as urban greening, rely on conversion of sensible heat to latent heat through evapotranspiration of water.…”
Section: Introductionmentioning
confidence: 97%
“…These relationships point to the conclusion that a drier land surface leads to worsened heat stress. Conversely, some recent studies have argued that droughts generally decrease heat stress because of the effect of reduced humidity 11 , while irrigation increases heat stress because of the effect of increased humidity [12][13][14][15] . This discrepancy has potentially major implications, as some climate adaptation actions intended to reduce heat stress, such as urban greening, rely on conversion of sensible heat to latent heat through evapotranspiration of water.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have mainly focused on the irrigation cooling effect on mean temperatures, aiming to reveal the contribution of irrigation to climate warming mitigation on global or regional scales (e.g., Cook et al., 2015; Qian et al., 2013; Sacks et al., 2009; Wu et al., 2018; Yang et al., 2016, 2020). With extreme heat events frequently occurring, a growing body of literature has attempted to evaluate the irrigation cooling effect on extreme temperatures, and it has been concluded that the impact on extreme temperatures is much more pronounced than that on mean temperatures, highlighting the role of irrigation in modulating extreme temperatures (e.g., Ambika & Mishra, 2022; Hauser et al., 2019; Hirsch et al., 2017; Mishra et al., 2020; Mueller et al., 2016; Thiery et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation is an important anthropogenic activity that accounts for approximately 70% of the total freshwater withdrawals globally (Wada et al., 2013) and generates distinct climate impacts (McDermid et al., 2023; Singh et al., 2018; Thiery et al., 2020). Numerous observational and modeling studies have explored the climatic effect of irrigation and yielded considerable achievements, showing that irrigation strongly affects the partitioning of surface turbulent heat fluxes, soil moisture, crop growth, and the coupling strength of land‐atmosphere interactions and therefore climate impacts (e.g., Ambika & Mishra, 2022; Bonfils & Lobell, 2007; Chen & Dirmeyer, 2019; Hirsch et al., 2017; Jha et al., 2022; Kang & Eltahir, 2018; Liu & Wang, 2023; Liu et al., 2021a, 2023; Mishra et al., 2020; Ozdogan et al., 2010; Qian et al., 2013; Thiery et al., 2017, 2020; Wang et al., 2021; Yang et al., 2020). Of the climatic effects of irrigation, the cooling effect is the most famous since it counteracts greenhouse‐gas‐induced warming (Bonfils & Lobell, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article in this journal, Ambika and Mishra (2022), hereafter AM22, employ modeling capabilities to investigate how a shift toward efficient irrigation (surface drip irrigation, specifically) will change moist heat stress regimes and water savings over the Indo‐Gangetic Plains of India. AM22 continues a useful stream of research oriented toward thermal comfort in a densely populated region globally, and how agricultural water management practices dictate these regimes in the region (Ambika & Mishra, 2019, 2020, 2021; Mishra et al., 2020).…”
Section: Introductionmentioning
confidence: 99%